An improved up-conversion nanoparticles-based immunochromatographic assay for rapid detection of zearalenone in cereals. (30th June 2023) - Chen, Yiyi; Lu, Haixi; Shi, Honghui; Zhu, Junli; Wang, Haifeng
Highlights: Synthesis and functionalization of the IUCNPs were described in detail. Synthesized IUCNPs have superior morphological structure and fluorescence properties. A novel IUCNPs-ICA for rapid detection of ZEN in cereals was proposed. IUCNPs-ICA has excellent sensitivity, accuracy, and specificity for detecting ZEN. IUCNPs-ICA demonstrated strong sample adaptability for practical application. Abstract: A novel improved up-conversion nanoparticles-based immunochromatographic assay (IUCNPs-ICA) was developed for the detection of zearalenone (ZEN). Lu 3+ -doped UCNPs were synthesized using the solvothermal method, and the UCNPs doped with 30 % Lu 3+ displayed optimal optical properties. The IUCNPs-ICA was subsequently developed for the detection of ZEN in cereals under optimized conditions. The detection time and limit of detection (LOD) were 10 min and 0.1 μg/L, respectively. Moreover, a good linear relationship was observed from 0 to 100 μg/L ZEN (r 2 = 0.9946) and high specificity for other mycotoxins. LODs in spiked maize and wheat reached 0.16 μg/kg, and recovery rates were 82.11–100.76 % and 79.64–98.51 %. There was good consistency between the results of IUCNPs-ICA, colloidal gold-ICA, and high-performance liquid chromatography (HPLC) in the detection of natural cereal samples. The collective results support the utility of IUCNPs-ICA as a reliable on-site screening method for ZEN residue analysis in various cereals.